Enantiorecognition phenomena in asymmetric synthesis - Yin, J; Jingda yin (2011)
This thesis is concerned with investigations into applications of double asymmetric induction and parallel kinetic resolution in asymmetric synthesis. Chapter 1 introduces enantiorecognition phenomena as a significant field in asymmetric synthesis. The main approaches in this field are described: double asymmetric induction, kinetic resolution, parallel kinetic resolution and dynamic kinetic resolution. Chapter 2 describes investigations into the use of double asymmetric induction as a mechanistic probe to elucidate the reactive conformation of enantiopure α,β-unsaturated esters (derived from Corey’s 8-phenylmenthol auxiliary) and hydroxamates [derived from (S)-N-1-(1'-naphthyl)ethyl-O-tert-butylhydroxylamine] upon conjugate addition. Chapter 3 describes investigations into the doubly diastereoselective organocatalytic intramolecular Michael cyclization of enantiopure enamides (derived from a 4-substituted-5,5-dimethyl-oxazolidin-2-one auxiliary) and α,β-unsaturated esters (derived from Corey’s 8-phenylmenthol auxiliary) using α-methylbenzylamine and its derivatives as the chiral catalysts. Chapter 4 describes investigations into parallel kinetic resolution of acyclic γ-amino-α,β-unsaturated esters utilising a 50:50 pseudoenantiomeric mixture of lithium amides. To highlight the synthetic utility of the resultant β,γ-diamino esters, their elaboration to a range of 5-substituted-4-amino-pyrrolidin-2-ones is demonstrated and a concise synthesis of natural product (±)-absouline is performed. Chapter 5 contains full experimental procedures and characterisation data for all compounds synthesised in chapters 2, 3 and 4.